Antimicrobial therapy of community-acquired pneumonia in a hospital setting (clinical and economic aspects) - O. V. Zhukova; O. V. Ruina; M. V. Khazov; S. V. Romanov (Фармакоэкономика, 2018)
The aim is to study the clinical and economic components of antimicrobial therapy (AMT) of community-acquired pneumonia (CAP) in a hospital ptactice.Materials and methods. Case reports of 48 patients with CAP hospitalized in FBU PMLC FMBA in the city of Nizhny Novgorod during 2016 were studied. All patients with CAP hospitalized  during that period were included in the study. A retrospective analysis of AMT was carried out based on the data from inpatient CAP cases.Results. We compared the real number of prescriptions of antimicrobial agents for CAP in this  hospital with the number of prescriptions required by the approved standards. We found that the  real numbers exceeded the recommended standards in the cases of severe CAP as follows: 2.1- fold for 3d generation cephalosporins, 1.3-fold for fluoroquinolones, and 1.3-fold for  carbapenems. Also notable was the use of ceftaroline fosamil – the 5th generation cephalosporin, which was not part of the standard therapy. Macrolides were not given to patients with severe CAP. In the treatment of CAP of moderate severity, fluoroquinolones were used 1.2 times more  often than that recommended by the standard protocol, 3d generation cephalosporins – 1.5  times more often; macrolides – 5 times less often, as well as carbapenems (not part of the  standard) and 5th generation cephalosporins (not part of the standard). The average duration  and cost of monotherapy of moderate CAP were: 10.5 days and 731.65 rubles for ceftriaxone;  9.1 days and 1353.00 rubles – for levofloxacin; 4 days and 11035.36 rubles – for ceftaroline  fosamyl; 9 days and 16,153.35 rubles – for ertapenem. Positive clinical outcomes were noted in  85% of cases. In 15% of cases, additional AMT was required. As a starting therapy for severe  CAP, antimicrobial monotherapy was prescribed in 89.3% of cases. Its efficacy was 0.920. The treatment regimen was changed in two cases.Conclusion. The present findings, namely the discrepancy between the real number of AMT prescriptions and the standard recommendations might be due to an ineffective previous  outpatient treatment and prolonged duration of the disease. It is important to note that the  treatment standard was adopted in 2012. Since then, a number of novel effective AMT agents  have been approved for clinical use: for example, ceftaroline fosamil – cephalos (cephalosporin of the 5th generation) is approved for the treatment of CAP, incl. in children from 2 months of age.  There is also a change in the structure of the CAP pathogens that involves bacterial associations  and the emergence of AMT resistant bacteria. The widespread use of macrolides inevitably leads  to the development of new resistant strains. According to the published reports, the following  species play an increasing role in the etiology of CAP: Streptococcus pneumoniae, Haemophilus  influenzae, and also the associations S. pneumoniae-H. Influenzae and S. pneumoniae-M.  pneumoniae. Associations of pathogens are observed in more than 60% of patients with CAP.